Mapping of Various Quality Management System Model to ISO 9001:2015 - Ramadan, Riski; Puspa Negara, Kartika; Wijatmiko, Indradi (KnE Social Sciences, 2024)
Measurement of Quality Management Systems (QMS) in construction projects is very important to assess the fulfillment of quality standards. A comprehensive and up-to-date standard setting is paramount. Much research has been done to develop a Quality Management System (QMS), but only focused on the quality management system in general by means of interviews and statistics. There are still only a few studies that focus on determining quality variables based on ISO 9001:2015, but they do not consider other Quality Management Systems (QMS) to obtain variables that are not in ISO 9001 2015. This research aimed to map out ISO 9001:2015 to find additional variables that are not present inside it. Six Sigma, Deming, Total Quality Management (TQM), Quality Management System (QMS), Baldrige Performance Excellence Framework, and LEAN Manufacturing are models for developing Quality Management Systems (QMS) that are widely applied in the construction industry today. This research produced eight additional variables as audit materials, which were expected to make ISO 9001:2015 better in its application and development in construction services. The eight variables were breaking down barriers between departments, eliminating pressure, eliminating arbitrary numerical targets, respecting people, contributing to society, reducing cycle time, increasing process transparency, and focusing on global process control. This research provides factors from a more varied and up-to-date quality management system that complements ISO 9001:2015 Keywords: mapping, Measurement of Quality Management System (QMS)